ANALISIS KUALITAS PELAYANAN PUBLIK DI DESA KARANGGEGER KECAMATAN PAJARAKAN KABUPATEN PROBOLINGGO - Aris Subekti; Sunairi Hariyanto (Jurnal Bina Bangsa Ekonomika, 2022)
Public service or service to the community is an important element that can be used as an indication of the success of government leadership. Similarly, the national reform movement, which does not mean anything if the service to the public mash is less feasible. In addition, to create "good governance" which aspect of accountability is a principle that must take precedence over the implementation of government, therefore, public services that are passed such as public sector excellent services are an obligation that must be done immediately. Suharto (2005) stated, "a characteristic of the process of building social welfare including complete and thorough with the meaning of all social aspect services held always treat consumers of applicants or beneficearies as a whole human being, either in the sense of an individual or group, which is not separated from the socio-cultural environmental system". The type of research conducted is qualitative descriptive qualitative with the aim of getting an appropriate description or depiction of the problem or research topic, which in this study the topic is the quality of public service in the village office. Data is explained and presented systematically in accordance with the reality on the ground or in accordance with the facts so as to provide an objective depiction of factual conditions rather than topics or objects of study in order to understand the quality of public services and factors that inhibit the improvement of the quality of public services in Karanggeger Village of Probolinggo Regency. The results showed that the acquisition of public service quality in Karanggeger Village earned performance in service units with service value "C" or categorized as "GOOD ENOUGH". Based on the results of IKM conversion the value is 74.50, and the score of each quality is 2.98 using a scale interval of 2.60 - 3.064. Based on the details, as many as 6 elements of 9 elements get the category QUITE GOOD. While the service with the category "GOOD" there are as many as 3 elements of 9 elements. While the factors that hamper the quality of public services in Karanggeger Village are punctuality and speed when giving layaan and low human resources who are competent to operate online devices